Bacillus sp. alone or combined with salicylic acid inhibited Trichoderma spp. infection on harvested white Hypsizygus marmoreus - Yang, Xiuqing; Li, Tianhao; Liu, Yu; Gu, Yuyi; Li, Jing; Wang, Chaoping; Zhao, Longgang; Wang, Xiaofeng; Li, Wenxiang; Sun, Yanan; Cheng, Fansheng; Zhu, Dan (Frontiers in Microbiology, 2024)
White Hypsizygus marmoreus is a popular edible mushroom. It is rich in nutrition and flavor but vulnerable to fungal disease, resulting in nutrient loss and aging. In this study, the pathogenic fungus Trichoderma spp. BBP-6 and its antagonist Bacillus sp. 1-23 were isolated and identified. The negative effects caused by this pathogen were judged by detecting a series of changes in the infected white H. marmoreus. The effects of Bacillus sp. 1-23 on Trichoderma spp. BBP-6 and the infected white H. marmoreus were detected. The effect of Bacillus sp. 1-23 treatment combined with salicylic acid (SA) was also considered. The results showed that Trichoderma spp. BBP-6 could affect the activities of antioxidant enzymes PAL, POD, CAT, SOD, GR, PPO, and APX to interfere with the stability of the white H. marmoreus antioxidant enzyme system and cause the mushroom severe browning and nutrition loss, as well as general quality deterioration.Trichoderma spp. BBP-6 directly. SA reinforced this inhibitory. Bacillus sp. 1-23 alone or combined with SA could help white H. marmoreus from the Trichoderma spp. BBP-6 infection to effectively maintain nutrients, restore and stabilize the antioxidant system, and reduce the production of malondialdehyde, superoxide anion and hydrogen peroxide. Thus, such treatments could be considered potential methods to alleviate damage from disease and extend the shelf life of white H. marmoreus.